Influence of starvation on the critical swimming behaviour during ontogenyof the Senegalese sole (Solea senegalensis) and its relationship with RNA/DNA ratios - Faria, Ana Margarida (2012)
Food availability can affect larval survival directly through starvation and indirectly through the effects on larval growth rate, swimming performance and vulnerability to predators. In the present study we evaluate the effects of starvation on growth, nutritional condition and swimming behaviour of the Senegalese sole (Solea senegalensis) throughout ontogeny (8 to 14 days after hatching). Biochemical analysis (RNA/DNA ratios) and behavioural experiments (critical swimming speed, Ucrit) were conducted on larvae reared under 3 feeding treatments: fed ad libitum, deprived of food for 48 hours and deprived of food for 96 hours. Growth was significantly affected by feeding treatment, while only slight decreases in RNA/DNA ratio and swimming performance were registered. Late stage larvae of the three feeding treatments had slower critical speeds than the pre-flexion and flexion stages, which is probably related to the benthic lifestyle acquired by the species at the end of the larval period. These physiological and behavioural changes are in accordance with previous results, which show that flatfish larvae are more resistant to starvation than pelagic species and that they become less active later in development.